Enabling women to access preferred methods of contraception: a rapid review and behavioural analysis - Abimbola A. Ayorinde; Felicity Boardman; Majel McGranahan; Lucy Porter; Nwamaka A. Eze; Anna Sallis; Rosanna Buck; Alison Hadley; Melissa Ludeke; Sue Mann; Oyinlola Oyebode (BMC, 2021)
Abstract Background Many pregnancies in the UK are either unplanned or ambivalent. This review aimed to (i) explore barriers and facilitators to women choosing and accessing a preferred method of contraception in the United Kingdom, and (ii) identify opportunities for behavioural interventions based on examination of interventions that are currently available nationally. Methods Three databases were searched, and experts contacted to identify grey literature for studies presenting barriers and facilitators to women choosing and accessing a preferred method of contraception, conducted in the UK and published between 2009 and October 2019. Information on barriers and facilitators were coded into overarching themes, which were then coded into Mechanisms of Actions (MoAs) as listed in the Theory and Techniques Tool. National interventions were identified by consulting stakeholders and coded into the Behaviour Change Wheel. The match between barriers/facilitators and intervention content was assessed using the Behaviour Change Wheel. Results We included 32 studies and identified 46 barrier and facilitator themes. The most cited MoA was Environmental Context and Resources, which primarily related to the services women had access to and care they received. Social Influences, Beliefs about Consequences (e.g., side effects) and Knowledge were also key. The behavioural analysis highlighted four priority intervention functions (Modelling, Enablement, Education and Environmental Restructuring) that can be targeted to support women to choose and access their preferred method of contraception. Relevant policy categories and behaviour change techniques are also highlighted. Conclusions This review highlights factors that influence women's choices and access to contraception and recommends opportunities that may be targeted for future interventions in order to support women to access preferred contraception. Registration Protocol was registered with PROSPERO (an international database of prospectively registered systematic reviews in health and social care) in December 2019, CRD42019161156 .